ETF arbitrage under liquidity mismatch - Kevin Pan; Yao Zeng (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
A natural liquidity mismatch emerges when liquid exchange traded funds (ETFs) hold relatively illiquid assets. We provide a theory and empirical evidence showing that this liquidity mismatch can reduce market efficiency and increase the fragility of these ETFs. We focus on corporate bond ETFs and examine the role of authorized participants (APs) in ETF arbitrage. In addition to their role as dealers in the underlying bond market, APs also play a unique role in arbitrage between the bond and ETF markets since they are the only market participants that can trade directly with ETF issuers. Using novel and granular AP-level data, we identify a conflict between APs' dual roles as bond dealers and as ETF arbitrageurs. When this conflict is small, liquidity mismatch reduces the arbitrage capacity of ETFs; as the conflict increases, an inventory management motive arises that may even distort ETF arbitrage, leading to large relative mispricing. These findings suggest an important risk in ETF arbitrage.
Keywords: G12; G14; G23; 330; Authorized participants; arbitrage; corporate bond; exchange-traded funds; liquidity mismatch